Improved material performance in floorball sticks Implementation of the Finite Element Method for helicallyfiber-oriented laminae in cylindrical hollow composites - Lindström, Mats (My University, 2015)
As a relatively novel sport, the amount of research specifically aimed at developing the game of floorball is limited. Despite the extensive research efforts being carried out related to composite materials few of the developed methods have yet to be adapted to the highly specific geometries and load-cases which apply to floorball stick shafts in play. Adaptation of these methods could ultimately lead to improved material performance and thus reduce the risk of injury for the athletes. The aim of this project was to develop a code base which can be implemented to investigate if improvements in the composition of the composite materials used in floorball stick shafts can be made to increase the impact resistance and thereby reduce risk of injury. Based on fundamental composite concepts such as homogenization, linear elasticity an coordinate system transformations an implementation of the Finite Element Method (FEM) was created and used for illustrating how varying the ply angles in helically oriented laminae affect the material properties in composite cylinders. Existing data from movement analysis measurements and experimental values of the elastic modulus for floorball sticks were used as a reference to validate the simulations. The simulations ultimately resulted in showing how deflections resulting from loads applied to cylindrical composites depend on the ply angles of the laminae. Even more important, however, is the reusability of the FEM implementation for other variations of the material structure such as volume fractions of fiber and matrix, lamina stacking sequence and ply angles, as well as different load-cases.
Keywords: Materialvetenskap; Grundläggande vetenskaper; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Fysik; Materials Science; Basic Sciences; Sustainable Development; Innovation & Entrepreneurship; Physical Sciences